Water Resources Planning and Management - Grafton, R. Quentin; Hussey, Karen (Cambridge : Cambridge University Press, 2011)
Water is an increasingly critical issue at the forefront of global policy change, management and planning. There are growing concerns about water as a renewable resource, its availability for a wide range of users, aquatic ecosystem health, and global issues relating to climate change, water security, water trading and water ethics. This handbook provides the most comprehensive reference ever published on water resource issues. It brings together multiple disciplines to understand and help resolve problems of water quality and scarcity from a global perspective. Its case studies and 'foundation' chapters will be greatly valued by students, researchers and professionals involved in water resources, hydrology, governance and public policy, law, economics, geography and environmental studies.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Water resources development; Watershed management; Water-supply